Co-sensitization to silkworm moth (Bombyx mori) and 9 inhalant allergens among allergic patients in Guangzhou, Southern China. - Baoqing Sun; Peiyan Zheng; Nili Wei; Huimin Huang; Guangqiao Zeng (PLoS ONE)
Objectives This study aimed to investigate the profile of sensitization to silkworm moth (Bombyx mori) and other 9 common inhalant allergens among patients with allergic diseases in southern China. Methods A total of 175 patients were tested for serum sIgE against silkworm moth in addition to combinations of other allergens: Dermatophagoides pteronyssinus, Dermatophagoides farinae, Blomia tropicalis, Blattella germanica, Periplaneta americana, cat dander, dog dander, Aspergillus fumigatus and Artemisia vulgaris by using the ImmunoCAP system. Correlation between sensitization to silkworm moth and to the other allergens was analyzed. Results Of the 175 serum samples tested, 86 (49.14%) were positive for silkworm moth sIgE. With high concordance rates, these silkworm moth sensitized patients were concomitantly sensitized to Dermatophagoides pteronyssinus (94.34%), Dermatophagoides farinae (86.57%), Blomia tropicalis (93.33%), Blattella germanica (96.08%), and Periplaneta americana (79.41%). Moreover, there was a correlation in serum sIgE level between silkworm moth and Dermatophagoides pteronyssinus (r = 0.518), Dermatophagoides farinae (r = 0.702), Blomia tropicalis (r = 0.701), Blattella germanica (r = 0.878), and Periplaneta americana (r = 0.531) among patients co-sensitized to silkworm moth and each of these five allergens. Conclusion In southern Chinese patients with allergic diseases, we showed a high prevalence of sensitization to silkworm moth, and a co-sensitization between silkworm moth and other five common inhalant allergens. Further serum inhibition studies are warranted to verify whether cross-reactivity exists among these allergens.